A study of energy from pineapple wastes; Torsional vivration of multidegree of freedom by computer programming; Design of inventory control systems; A comparative study of LPG against gasoline on an IC engine; Design of an open type refrigeration unit; Fatigue tests; Oil palm harvesting (infield transportation); Design of vacuum packaging machine [mikrofilem] - Mohd. Nawai Abd. Wahab; Mohd. Kamaludin Hussin; Mahabob Suib; Abdul Rahim Jaafar; Hashimuddin Jaafar; Lee, Chi Heng; Mohd. Ramli Mohd. Khan; Tay, Kim Yong (Kuala Lumpur : UTM, 1980)
Thesis (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1980